Palliative Care and the Family Caregiver: Trading Mutual Pretense (Empathy) for a Sustained Gaze (Compassion) - Goldsmith, Joy (Behav Sci (Basel), 2017)
In this conceptual piece, we survey the progress of palliative care communication and reflect back on a chapter we wrote a decade ago, which featured the communication concept of mutual pretense, first described by Glaser and Strauss (1965). This work will include an update on family caregivers and their role in cancer caregiving as well as a review of current palliative care communication curriculum available for providers. And finally, we will spotlight the conversation and research going forward on the subject of health literacy for all stakeholders; patients, families, providers, and systems. We feature one family’s story of incurable cancer and end of life to revisit the needs we identified ten years ago, which are still present. Goals for going forward in chronic and terminal illness are suggested in a health care context still too void of palliative care communication resources for providers, patients, and especially family caregivers.